The interpersonal communication skill of the unlicensed trekking guides - Purnawan, Jaini; Suadiyatno, Taufik (Mell Baou Publisher, 2025)
This study aims to explore the interpersonal communication skills of unlicensed trekking guides in Mount Rinjani National Park, Indonesia. As tourism expands in Lombok, communication plays a central role in ensuring satisfaction, safety, and positive cultural exchange. Effective communication is crucial in the case of trekking activities, which involve physical challenges and require both trust and cooperation between trekking guides and visitors. This research employed a qualitative method, in which the data were collected through interviews, observations, audio, and video recordings of five unlicensed trekking guides with varied educational backgrounds and experiences. The framework applied in this study is Joseph A. DeVito’s five indicators of interpersonal communication effectiveness: openness, supportiveness, positiveness, empathy, and equality. The findings showed that unlicensed trekking guides possess strong interpersonal communication abilities in practice, despite the absence of formal training or certification. Their skills help foster mutual understanding and enrich visitors’ experiences. However, challenges were also identified, including limited English vocabulary, low confidence, and gaps in intercultural competence. This research highlights the importance of structured communication training for trekking guides and offers insights for tourism educators and policymakers aiming to raise service quality and safety standards in Mount Rinjani National Park.